PENGARUH MEDIA GAMBAR TERHADAP KEMAMPUAN BAHASA ARAB ANAK USIA 5-6 TAHUN THE INFLUENCE OF MEDIA IMAGES ON ARABIC ABILITY OF CHILDREN AGE 5-6 YEARS - Putri Clawson; Dewi Purwati (P3M STKIP 'Aisyiyah Riau, 2020)
The purpose of this study was to determine how much influence the image media has on Arabic language skills of children aged 5-6 years at TK Aisyiyah Petapahan, Tapung District, Kampar Regency. This research uses a quantitative approach and the type of research is experimental. Experimental research is research that provides treatment of research variables (independent variables), then observes the consequences of these treatments on research objects (dependent variables). The sample in this study were all early childhood children in TK Aisyiyah Petapahan, Tapung Subdistrict, Kampar Regency, as many as 1 class, namely 17 children found in class B2, aged 5-6 years. Based on the results of data analysis and discussion in this study, the following conclusions can be drawn: Image media has an effect of 29.1% on Arabic language skills of children aged 5-6 years at TK Aisyiyah Petapahan, Tapung District, Kampar Regency. This shows the value of 29.1% is included in the high category. This value is obtained from the pre test and post test values. Where the total score obtained in pre-test was 325 with a percentage value of 47.8%, and the total score obtained in the post-test was 523 with a percentage value of 76.9%. So the magnitude of the influence of media images on Arabic language skills is 76.9% - 47.8% = 29.1%.